Hak-Hak Non Muslim dalam Pemerintahan: Konsep Dien wa Ni’mah dan Pluralisme Agama di Indonesia - ZA, Tabrani; Walidin, Warul (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
This paper aims to discuss the rights of non-Muslim citizens in Indonesia at government refers to the conception of the state of Dien wa Ni'mah. The main argument in this paper that the concept of Dien wa Ni'mah prioritize law as an important pillar can accommodate pluralism and contextual with the system of the Unitary State of the Republic Indonesia based on Pancasila. The research method used was a historical study, based on a comprehensive literature review from various sources in books and journals about the concept of Dien wa Ni'mah. The results of this study explain that Dien wa Ni'mah is a concept of the manifestation of Islam as a religious teaching that is Rahmatan Li al-Alamin and build human life through law as the main universal pillar, not only as the theological framework and spiritual principles of mankind, also in the life of society, nation and religion. So this concept accommodates the rights of non-Muslims in government by considering pluralism and democracy. Thus making the concept of Dien wa Ni'mah as the nation's perspective to the Civil Society will have an impact on the participation of all parties.